Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Mie Gacoan Tangerang - Pratama, Bagas Yadi; Hastasari, Ratih; Saputra, Wawan (CV Warnak Johanna Nusantara, 2025)
This study aims to determine the effect of price and product quality on consumer purchasing decisions at Mie Gacoan Tangerang. Intense competition in the culinary industry requires companies to understand the factors influencing purchasing decisions, with price and product quality being primary consumer considerations. The research population includes all consumers who have purchased Mie Gacoan at least once, with a sample size of 100 people taken using accidental sampling technique and the LemeShow formula. A quantitative method was applied in this study; respondent data was collected by distributing questionnaires and analyzed using IBM SPSS version 25. The results show that partially, price has a positive and significant effect on purchasing decisions with a value of 2.148; similarly, product quality has a positive and significant effect on purchasing decisions with a value of 11.941. Simultaneously, both variables together have a significant influence with a value of 266.863. The resulting regression equation is Y = (-13.209 + 0.263X1 + 1.193X2). An R Square value of 84.6% indicates that both variables together influence the purchasing decision. The remaining 15.4% is influenced by other factors outside of this study